Pengaruh Pengeluaran Pemerintah Sektor Kesehatan dan Bantuan Sosial Terhadap Kualitas Sumber Daya Manusia di Indonesia - Aldi Primananda; Yeniwati Yeniwati; Dwirani Puspa Artha (Universitas Negeri Padang, 2023)
The study aims to find out the effect of (1) government budgeting in health sector on quality of human resources in Indonesia (2) non cash food assistance programme on quality on human resources in Indonesia (3) smart indonesia programme on quality of human resources in Indonesia (4) government budgetin in health sector, non cash food assistance program and smart indonesia program on quality of human resources in Indonesia. This study uses secondary data which source of Badan Pusat Statistik Indonesia, DJPK Kemenkeu, Kemensos RI and PIP Kemendikbud. This study uses panel data analysis with Random Effect Model (REM) on 34 provinsi In Indonesia during 2018-2020. The result of the study are (1) Government budgeting in health sector has positively significant on quality of human resources (2) Non cash food assistance programme has positively insignificant on quality of human resources (3) Smart Indonesia Programme has negatively significant on quality of human resource (4) Government budgeting in health sector, Non cash food assistance programme and Smart Indonesia Programme have impact on quality of human resources.